Evaluation of the Accuracy of the Use of Intravesical Prostatic Protrusion Degree as the Predictor of Benign Prostatic Hyperplasia Management - Fellyana Putri; Mohammad Fariz (Jurnal Ilmu Kedokteran, 2024)
Managing symptoms of benign prostatic hyperplasia (BPH) is important but preventing the progression of the disease is also necessary. Medical therapy is commonly used to treat BPH as initial therapy. However, not every medical therapy is effective for treating BPH. Intravesical prostatic protrusion (IPP), a manifestation of BPH is used to evaluate BPH progression thus helping clinicians in choosing the effective treatment option. Patients with higher IPP degrees may experience more severe bladder outlet obstruction (BOO). They may not respond well to medical therapies, suggesting that IPP measurement can guide treatment decisions for BPH patients. This study evaluates the accuracy of using IPP degree as a predictor of BPH management by reviewing relevant literature. A comprehensive approach was undertaken, including the selection and filtering of articles from reputable databases and scholarly repositories using specific keywords related to the study's objectives. By measuring IPP degrees, the severity of clinical BPH can be categorized, allowing clinicians to choose effective treatment options and predict treatment outcomes.